Penerapan Model Pembelajaran Penemuan Terbimbing Suatu Upaya Meningkatkan Keterampilan Proses Sains Siswa - Karlina Rahmi; Zainuddin Zainuddin; Suriasa Suriasa (Berkala Ilmiah Pendidikan Fisika, 2013)
Preliminary observations on the school declared students' science process skills and ability to perform scientific work in the learning of physics have not been fully implemented. It can be seen from the observations of physics learning activity, interviews with physics teacher and results of student questionnaire. Guided discovery learning is a model of learning to train students in the science process skills and solving academic problem. This study used action research to describe the effectiveness of the application of the guided discovery learning model to improve students' science process skills. This study has shown (1) lesson plan implementation in each cycle is verry good; (2) assessment of students' science process skills increased in each cycle to be categorized verry good at the end of the cycle; (3) improvement learning outcomes student and complete; and (4) student responses is categorized as good. So concluded that the application of the guided discovery learning model in straight motion materials was effective for improving science process skills, at the same time results of learning and scientific attitude of students of class X-A  SMAN 1 Kandangan in 2012-2013.